Effect of Time Variation and Mole Ratio on Biodiesel Production from Coconut Oil Using CaO Catalyst via Transesterification Method - Grace Trinita; Dessy Agustina Sari; Muhammad Fahmi Hakim (Universitas Muhammadiyah Purwokerto, 2025)
The use of fossil fuels by the world resulted in an impulse for the use of renewable energy sources including biodiesel. In the present investigation, the objective is to find out the best conditions of coconut oil transesterification into biodiesel for transesterification source of the homogeneous basic catalyst of CaO. The experiments were conducted by varying the reaction time (100, 120 and 150 min), the molar ratio of coconut oil to methanol (1:12, 1:15 and 1:18), and temperature (60°C) as a fixed level in the experimental plan The optimum condition of reaction was at 1:15 molar ratio and a time of 120 min producing biodiesel that meets the (SNI 7182:2015) Indonesian National Standard with properties; density was 858.20±26.95 kg/m3, viscosity was 2.64±0.22 cSt, methyl ester content was 96.14±0.73%. Furthermore, the utilization of CaO catalyst not only improved the quality of biodiesel, but also possessed economic and environmental benefits compared with traditional homogeneous catalysts. These results confirm the feasibility of using coconut oil as a cheap and sustainable raw materials for biodiesel production as well as their effective use in larger scale production of renewable energy.